2023
DOI: 10.1021/acsapm.3c01209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced High-Temperature Capacitive Energy Storage by 0.55Bi0.5Na0.5TiO3-0.45(Bi0.2Sr0.7)TiO3 Nanofibers in Polyetherimide Nanocomposites

Yuan Liu,
Hang Luo,
Hao Xiong
et al.

Abstract: The low discharge energy density and operation temperature of dielectrics limit the integration application of capacitors under extreme environment conditions. In order to reduce the dielectric loss of Bi 0.5 Na 0.5 TiO 3 , 0.55Bi 0.5 Na 0.5 TiO 3 -0.45(Bi 0.2 Sr 0.7 )TiO 3 (BNT-BST) nanofibers with optimized diameter were synthesized and utilized to improve the high-temperature capacitive energy storage of polyetherimide (PEI) nanocomposites. Benefiting from the introduction of nanofibers, the leakage current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…From the perspective of improving ε r , scholars have proposed 0–3 type ceramic/polymer composite materials. Numerous studies have shown that this model of composite material is the most direct and effective in improving dielectric and energy storage properties ,,,,− and is an ideal dielectric material for energy storage applications. In addition to the connectivity between the two, the properties of the composite films are largely influenced by several variables, such as the properties of the polymer matrix (semicrystalline, amorphous, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of improving ε r , scholars have proposed 0–3 type ceramic/polymer composite materials. Numerous studies have shown that this model of composite material is the most direct and effective in improving dielectric and energy storage properties ,,,,− and is an ideal dielectric material for energy storage applications. In addition to the connectivity between the two, the properties of the composite films are largely influenced by several variables, such as the properties of the polymer matrix (semicrystalline, amorphous, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the connectivity between the two, the properties of the composite films are largely influenced by several variables, such as the properties of the polymer matrix (semicrystalline, amorphous, etc. ), the size of the ceramic filler (micrometer, nanometer), the dimensionality of the ceramic filler (zero-dimensional, one-dimensional ,,, ), and the method of preparation used (spin-coating, ,, , hot-pressing, etc.). Recently, ternary composite ceramic/polymer composite films (zero-dimensional fillers doped into blended polymers) have been reported. , For example, Liu et al prepared a PVDF/PMMA/TiO 2 composite film by melting, blending, and blow molding processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of modern power electronics technology has put forward higher requirements for the energy storage performance of capacitors. Polymer-based thin film capacitors play an essential role in modern electronic equipment and electricity systems due to the advantages of rapid discharge rate, high voltage resistance, high reliability, lightweight, and low cost. For example, the most common commercial film capacitors use bioriented polypropylene (BOPP) as the dielectric material and the capacitors behave with low dielectric loss (∼0.0003), high breakdown strength (∼600 MV/m), and ultrahigh room temperature charge/discharge efficiency (>90%). However, the low dielectric constant (∼2.2) of PP makes it difficult to improve the energy storage density (∼2 J/cm 3 ) of thin film capacitors, which has become an obstacle for miniaturization, integration, and high functionality of the electronic and electrical equipment.…”
Section: Introductionmentioning
confidence: 99%